An Examination of Austen As A Discrete Feminist in Persuasion - S. Madhura Bashini (ILN Journal: Indian Literary Narratives, 2024)
Many feminists, including Virginia Woolf, consider Jane Austen as the 'Angel of the House'—a woman who conforms to the patriarchal values of her time. This paper aims to portray Jane Austen in a new light, as a distinct voice advocating for feminine liberation. Upon scrutinising Austen's Persuasion more closely, this article uncovers numerous instances in which Austen endeavours to empower her female characters with agency. While Austen doesn't explicitly challenge patriarchal customs, she employs subtle references to challenge the prevalent gender roles in her society. A woman writer in Austen's time would encounter numerous criticisms and social exclusion if she dared to challenge the patriarchal system. And Austen, a woman writer from a middle-class family with a lack of connections and money, could do nothing but write in a manner that conforms to social values. But being a woman and a writer with integrity, Austen chose to leave bits and pieces of the truth and bits and pieces of resistance between the leaves of her books. This article aims to highlight the significant modes of resistance after careful contemplation.